Competition Policy in the Conditions of Pandemics and New EU Strategic Priorities - Marinov, Eduard (Economy and Business Yearbook, 2022)
In times of crisis and transition, the proper and efficient functioning of the single market is of the utmost importance. The article discusses the EU response to the specific challenges faced by the single market posed by the global pandemic through the prism of competition policy, with a special focus on the situation in Bulgaria during the crisis.